Awareness of Menstrual Hygiene Management Rights and Perception of Risks, Self-Efficacy, and Behavior - Yadav, Ram Naresh; Joshi, Shrijana; Park, Ji Sun (Journal of Nepal Health Research Council, 2024)
Background: Menstrual Hygiene Management stands as a critical health concern for girls entering reproductive age on a global scale. This transition often induces fear and anxiety due to inadequate knowledge about menstruation and a lack of resources to comprehend bodily changes. Notably, school-aged girls in marginalized communities face formidable barriers to MHM, given the insufficient facilities, supplies, and awareness in educational institutions. Methods: A Mixed method study was conducted adopting a mixed-methods approach. It engaged 562 respondents across five local levels of Bajura district, including three municipalities (Badimalika, Budhiganga, and Tribeni) and two rural municipalities (Gaumul and Khaptad Chhedaha). Results: The study unveiled over 90% awareness on on five out of seven MHM rights related statements and over 85% self-efficacy on 5 out of 8 statements regarding MHM among female adolescent respondents. However, their actual practices fell short of expectations, marked by the prevalence of restrictive norms and perceived risks pertinent to MHM. Notably, 27% (N=154) expressed fear of divine consequences for not adhering to menstrual customs. Malpractices were observed, including 66% using cloth during menstruation, inadequate pad changing frequencies, and some girls staying in Chhaugoth during menstruation. Despite a high awareness (97%) of menstrual rights, behavioral practices did not consistently align with this awareness. Conclusions: The study highlights high awareness and self-efficacy in menstrual hygiene management among female adolescents, yet challenges persist due to cultural norms, perceived risks, and insufficient infrastructure, necessitating multifaceted solutions for behavioral change and access to resources. Keywords: Adolescent girls; awareness on MHM rights; behaviour; perception of risks; self-efficacy.